Delineating the Role of the msaABCR Operon in Staphylococcal Overflow Metabolism - G C, Bibek; Sahukhal, Gyan S.; Elasri, Mohamed O. (Frontiers in Microbiology, 2022)
Staphylococcus aureus is an important human pathogen that can infect almost every organ system, resulting in a high incidence of morbidity and mortality. The msaABCR operon is an important regulator of several staphylococcal phenotypes, including biofilm development, cell wall crosslinking, antibiotic resistance, oxidative stress, and acute and chronic implant-associated osteomyelitis. Our previous study showed that, by modulating murein hydrolase activity, the msaABCR operon negatively regulates the proteases that govern cell death. Here, we report further elucidation of the mechanism of cell death, which is regulated by the msaABCR operon at the molecular level in the USA300 LAC strain. We showed that deletion of msaABCR enhances weak-acid-dependent cell death, because, in the biofilm microenvironment, this mutant strain consumes glucose and produces acetate and acetoin at higher rates than wild-type USA300 LAC strain. We proposed the increased intracellular acidification leads to increased cell death. MsaB, a dual-function transcription factor and RNA chaperone, is a negative regulator of the cidR regulon, which has been shown to play an important role in overflow metabolism and programmed cell death during biofilm development in S. aureus. We found that MsaB binds directly to the cidR promoter, which represses expression of the cidR regulon and prevents transcription of the cidABC and alsSD operons. In addition, we observed that pyruvate induced expression of the msaABCR operon (MsaB). The results reported here have enabled us to decipher the role of the msaABCR operon in staphylococcal metabolic adaption during biofilm development.